Factors Affecting Adoption of Home Science Practices Disseminated Through Rural Awareness Work Experience (RAWE) - Kaur, Sandeep; Mann, Sukhdeep Kaur; Kaur, Manjot (Indian Journal of Extension Education, 2021)
The study was aimed to assess the adoption status of home practices and to identify the various factors affecting adoption and non-adoption of practices disseminated through rural awareness work experience programme. The study was conducted in four villages of Ludhiana district of Punjab state, where RAWE programme was conducted during the year2013-14 to 2016-17. A total of 120 respondents constituted the sample of the study. Data were collected through a well- structured and pre tested interview schedule. Highest adoption status was achieved by the practices under ‘Food and Nutrition’ followed by practices under ‘Human Development’ discipline. Various factors affecting adoption of differentpractices as reported by the respondents were personal interest, saves resources and provides satisfaction. Major factors affecting non-adoption of practices were lack of interest, lack of resources, non-availability of raw material and inadequate skill retention. Majority of the respondents suggested that practices imparted under RAWE programme should becost effective, for better adoption. Respondents also suggested that to increase adoption rate of home science practices, duration of RAWE should be increased, so that respondents can get sufficient time to learn new practices.